Preparation method of carbon packaged porous hard carbon / Si composite negative electrode material
By adopting the preparation method of carbon-encapsulated porous hard carbon/Si composite material, the problems of powderization and poor electrical contact caused by volume expansion during the cycle of lithium-ion batteries are solved, and the cycle stability and electrochemical properties of the batteries are significantly improved.
Patent Information
- Application Number
- CN202411713055.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The existing silicon-based anode materials have pulverized due to volume expansion during the circulation of lithium-ion batteries, poor electrical contact and unstable solid electrolyte interfaces, affecting battery performance.
The preparation method of carbon-encapsulated porous hard carbon/Si composite material is adopted. By compositeing nanosilicon with porous hard carbon, and packaging and pretreatment is carried out using carbon nanospheres, cetyl trimethyl ammonium bromide, ammonia water, m-aminophene and formaldehyde solutions, a stable carbon encapsulation layer is formed to avoid exposure of silicon particles and side reactions.
It significantly improves the cycle stability and electrochemical properties of lithium-ion batteries, reduces the risk of silicon volume expansion and electrolyte contact, and extends the battery's service life.
Smart Images

Figure CN119601622A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new energy materials, and in particular relates to a method for preparing a carbon-encapsulated porous hard carbon / Si composite negative electrode material. Background Art
[0002] The most widely used negative electrode material for lithium-ion batteries today is graphite. Graphite negative electrode materials have the advantages of low lithium insertion potential and good cycle stability. However, the theoretical specific capacity of graphite is low and cannot meet the needs of current scientific and technological development. With the discovery of silicon materials, it has become one of the most promising substitutes for graphite. Silicon-based materials undergo alloying reactions during the charging and discharging process, and the theoretical specific capacity is as high as 4200mAh·g -1 , while the lithium insertion potential is relatively low. However, silicon-based materials will expand in volume during the charge and discharge process, resulting in pulverization of active materials and poor electrical contact between active materials and current collectors, which leads to instability of the solid electrolyte interface (SEI) and severe capacity decay. Improving the cycle stability of silicon-based negative electrode materials is crucial for the practical application of silicon. Researchers have used various methods to improve the electrochemical performance of silicon-based materials, such as nano-structuring of silicon-based materials, porous silicon structure design, carbon coating, and composite with other materials.
[0003] However, the problems existing in the current production and application process of silicon-based negative electrode materials have seriously limited their commercial application. The composite negative electrode materials fall off and agglomerate during the charge and discharge process, which affects the performance of lithium-ion batteries. The synthesis method that is simple to operate, has low energy consumption, does not pollute the environment, and can be mass-produced is also the key to whether silicon-based negative electrode materials can be put into commercial application. The preparation of carbon-silicon composite materials mostly uses high molecular organic carbon such as asphalt, phenolic resin, and glucose as carbon sources. This process uses organic adhesives in the preparation process to achieve a better composite effect. In the encapsulation and coating process, CVD (CN118610384A, CN118117082B), metal deposition (CN118645600A), etc. are often used to encapsulate silicon-based materials to synthesize core-shell structures and yolk-shell structures (CN115377399B), but these processes are prone to introduce redundant substances during the preparation process, and problems such as impurity removal need to be solved urgently. In addition, the cumbersome preparation process and high equipment prices make it unsuitable for large-scale production.
[0004] In order to solve the above problems, relevant workers have done a lot of research. Many of them use inorganic large-skeleton porous carbon, i.e. wood activated carbon, modified coal-based activated carbon, porous hard carbon, etc. as carbon sources and composite with nano-silicon (patent numbers: US20230219819A1, CN117317205A, CN117476919A), etc. Although the above modification methods have significantly improved the cycle stability of the battery, the side reactions between the active silicon particles and the electrolyte during the cycle of the lithium-ion battery in the silicon-based negative electrode material, resulting in particle pulverization, gas production, and structural collapse, are still a major problem. Therefore, how to reduce the exposure of silicon particles, reduce the occurrence of side reactions, and improve structural stability are prominent issues that need to be solved urgently. Summary of the invention
[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a method for preparing a carbon-encapsulated porous hard carbon / Si composite negative electrode material.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing a carbon-encapsulated porous hard carbon / Si composite negative electrode material comprises the following steps:
[0008] (1) Sawdust and potassium hydroxide powder are placed in water, sealed, stirred, dried, and then calcined under protective gas. The calcined product is then soaked in hydrochloric acid, rinsed, and finally dried to obtain porous hard carbon.
[0009] (2) dissolving nano-silicon in a mixture of anhydrous ethanol and water to obtain a nano-silicon solution; dispersing porous hard carbon in a mixture of anhydrous ethanol and water to obtain a porous hard carbon dispersion solution;
[0010] (3) mixing the nano-silicon solution and the porous hard carbon dispersion solution to obtain a porous hard carbon / Si composite material mixed solution;
[0011] (4) adding carbon nanospheres, hexadecyltrimethylammonium bromide, ammonia water, m-aminophenol and formaldehyde solution to the porous hard carbon / Si composite material mixed solution continuously stirred in step (3), sealing, stirring, standing, centrifuging, washing and drying to obtain a carbon-encapsulated porous hard carbon / Si composite material precursor;
[0012] (5) calcining the carbon-encapsulated porous hard carbon / Si composite material precursor in a protective gas to obtain a carbon-encapsulated porous hard carbon / Si composite material;
[0013] (6) The carbon-encapsulated porous hard carbon / Si composite material, the conductive agent, and the binder are mixed to prepare a slurry, and then coated on a current collector and dried to obtain a negative electrode sheet for a lithium-ion battery.
[0014] As a preferred embodiment of the present invention, the mass ratio of the carbon nanospheres, hexadecyltrimethylammonium bromide, ammonia water, m-aminophenol, formaldehyde solution and nano-silicon is (1-10):(1-6):(6-15):(2-7):(4-15):1.
[0015] As a preferred embodiment of the present invention, the diameter of the carbon nanospheres is 20-100 nm, the mass percentage of ammonia in the ammonia water is 38%, the mass percentage of formaldehyde in the formaldehyde solution is 40%; the pore size of the porous hard carbon is 500 nm-1 μm.
[0016] The carbon nanospheres have a diameter of 20 to 100 nm, which is conducive to entering the porous hard carbon channels and interlacing with nano-silicon, promoting the ions and electrons of the battery to better combine with the silicon base of the negative electrode material during the charge and discharge process. If the diameter of the carbon nanospheres is larger than this range, the carbon nanospheres cannot enter the porous hard carbon channels and can only stay outside the porous hard carbon and cannot play a conductive role. If the diameter of the carbon nanospheres is smaller than this range, although they can enter the porous hard carbon channels, the effect of improving the battery's rate performance is limited.
[0017] As a preferred embodiment of the present invention, the order of adding the carbon nanospheres, hexadecyltrimethylammonium bromide, ammonia water, m-aminophenol and formaldehyde solution to the porous hard carbon / Si composite material mixed solution is carbon nanospheres, hexadecyltrimethylammonium bromide, ammonia water, m-aminophenol, and formaldehyde solution, which can ensure that all materials are fully dispersed or dissolved, otherwise the conductivity of the negative electrode material and the rate performance of the battery are not significantly improved, and the silicon volume expansion can only be slightly alleviated. The interval time for adding the materials is 10 to 180 minutes, and the reaction continues for 4 to 12 hours after the materials are added.
[0018] The present invention uses hexadecyltrimethylammonium bromide, ammonia water, m-aminophenol and formaldehyde solution to carry out encapsulation pretreatment on nano-silicon and carbon nano-balls entering the porous hard carbon pores. The ammonia water provides conditions for the polycondensation reaction of m-aminophenol and formaldehyde, and the hexadecyltrimethylammonium bromide can form micelles to encapsulate m-aminophenol and formaldehyde into a whole during the polycondensation process, thereby avoiding the agglomeration of Si nano-particles and preventing the polycondensation reaction from being carried out only on the surface of silicon particles, and reducing the repulsive force between particles with the same charge. If the hexadecyltrimethylammonium bromide is not added, the coating layer will be directly on the surface of the Si particles, each Si particle will serve as a core, and the carbon layer will serve as an outer shell, so that the encapsulation effect cannot be achieved, and the volume expansion of silicon cannot be alleviated and the electrochemical properties of the battery cannot be significantly improved.
[0019] As a preferred embodiment of the present invention, the mass ratio of the sawdust to the potassium hydroxide powder is (1-2):(1-3); after the sawdust and the potassium hydroxide powder are put into water, the concentration of potassium hydroxide is 0.4-2.0 mol / L.
[0020] As a preferred embodiment of the present invention, in step (1), calcination specifically comprises: heating from room temperature to 300-500°C at a heating rate of 5°C / min and keeping the temperature for 0.2-1h, then heating to 700-900°C and keeping the temperature for 0.5-3h.
[0021] As a preferred embodiment of the present invention, in the step (1), the soaking time in hydrochloric acid is 12 to 24 hours, and the concentration of hydrochloric acid is 0.5 to 2 mol / L.
[0022] The pore size of the porous hard carbon is 500nm-1μm.
[0023] As a preferred embodiment of the present invention, in the step (2), the volume ratio of anhydrous ethanol to water is (1-5):1.
[0024] The present invention uses a mixed solution of anhydrous ethanol and water to disperse or dissolve porous hard carbon or nano-silicon. If only water is used, the dispersion of nano-silicon on the surface or in the pores of the porous hard carbon will be unsatisfactory, which will eventually lead to a significant decrease in the electrochemical properties of the lithium-ion battery. Alternatively, using only ethanol is not conducive to the successful preparation of negative electrode materials.
[0025] As a preferred embodiment of the present invention, in the step (3), the mass ratio of nano-silicon to porous hard carbon is (1-3):1.
[0026] As a preferred embodiment of the present invention, in step (5), calcination specifically comprises: heating from room temperature to 300-500°C at a heating rate of 5°C / min and keeping the temperature for 0.1-1h, then heating to 700-900°C and keeping the temperature for 1-3h.
[0027] As a preferred embodiment of the present invention, the conductive agent is conductive carbon black; the binder is sodium alginate; the mass ratio of the carbon-encapsulated porous hard carbon / Si composite material, the conductive agent, and the binder is 6:2:2.
[0028] As a preferred embodiment of the present invention, the thickness of the slurry on the current collector is 15 microns.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The sawdust carbon source of the present invention has a higher theoretical specific capacity than traditional graphite. At the same time, the hard carbon material has a stable structure, good cyclability, and can work at a relatively low temperature. The porous hard carbon can evenly embed the nanoparticles in the pore channels of the porous hard carbon, thereby buffering the volume expansion of the silicon particles during the charge and discharge process.
[0031] (2) The present invention uses carbon nanospheres, hexadecyltrimethylammonium bromide, ammonia, m-aminophenol and formaldehyde to put carbon nanospheres into the pores of porous hard carbon, restricting silicon inside the hard carbon, effectively alleviating silicon volume expansion and failure, and shortening the transmission distance of lithium ions. At the same time, the hard carbon can also improve the conductivity of the electrode plate. The electrochemical properties of lithium-ion batteries are significantly improved, and there is great development prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 These are SEM images of the porous hard carbon / Si composite material prepared in Example 1, (a) is a low-magnification SEM image; (b) is a medium-magnification SEM image; and (c) is a high-magnification SEM image.
[0033] Figure 2 These are SEM images of the carbon-encapsulated porous hard carbon / Si composite material prepared in Example 1, (a) is a low-magnification SEM image; (b) is a medium-magnification SEM image; and (c) is a high-magnification SEM image.
[0034] Figure 3 XRD curves of nano-silicon, porous hard carbon, porous hard carbon / Si composite material and carbon-encapsulated porous hard carbon / Si composite material prepared in Example 1.
[0035] Figure 4 The lithium-ion battery assembled with the additional materials prepared in Example 1 and Comparative Examples 1-4 was subjected to 200 mA g -1 Cycling performance curves under different current densities.
[0036] Figure 5 Cycle rate performance curves of lithium-ion batteries assembled with the additional materials prepared in Example 1 and Comparative Example 3 at different current densities.
[0037] Figure 6 The lithium-ion battery assembled with the materials prepared in Example 1 and Comparative Example 3 was -1 Long cycle performance curve under current density. DETAILED DESCRIPTION
[0038] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0039] Example 1
[0040] A method for preparing a negative electrode material for a lithium-ion battery by carbon encapsulating porous hard carbon / Si composite, specifically comprising the following steps:
[0041] (1) Weigh 10 g of birch sawdust and place it in 250 mL of a 1 mol / L potassium hydroxide solution. Cover the beaker with plastic wrap, control the temperature to 80 °C, and stir on a magnetic stirrer for 8 h. After the reaction is completed, pour off the upper solution, add deionized water and rinse repeatedly 2-3 times. Dry the sawdust in an 80 °C drying oven for 12 h, place it in a tubular furnace, heat it to 300 °C at a rate of 5 °C / min under an argon atmosphere, and keep it warm for 0.5 h. Then continue to heat it to 800 °C and start calcining. Calcinate for 1 h, soak the intermediate product in 1 mol / L hydrochloric acid for 24 hours, rinse it with deionized water, and finally dry it to obtain a porous hard carbon material. The pore size of the porous hard carbon is between 500 nm and 1 μm.
[0042] (2) 0.3 g of nano-silicon was placed in a mixed solution of 40 mL of anhydrous ethanol and 10 mL of deionized water, and ultrasonically vibrated for 1 hour to obtain a nano-silicon dispersion solution; at the same time, 0.2 g of porous hard carbon was placed in a mixed solution of 40 mL of anhydrous ethanol and 10 mL of deionized water, and ultrasonically vibrated for 1 hour to obtain a porous hard carbon dispersion solution.
[0043] (3) The porous hard carbon dispersion solution is stirred in a magnetic stirrer, and the nano-silicon dispersion solution is slowly added and stirred for 2 hours to obtain a porous hard carbon / Si composite material mixed solution, which is stirred continuously for subsequent steps.
[0044] (4) Add 0.9 g of carbon nanospheres to the continuously stirred porous hard carbon / Si composite material mixed solution, stir for 2 h, then add 0.4 g of hexadecyltrimethylammonium bromide (CTAB); continue stirring for 20 min, then add 4 mL of ammonia water and 1.2 g of m-aminophenol; continue stirring for 30 min, then add 2.4 mL of formaldehyde solution, seal, continue stirring at a reaction temperature of 40°C for 8 h, let stand for 4 h, centrifuge, wash the intermediate product twice with anhydrous ethanol, and dry it in a drying oven at 80°C for 12 h to obtain a carbon-encapsulated porous hard carbon / Si composite material precursor, wherein the mass percentage of ammonia in the ammonia water is 38%, and the mass percentage of formaldehyde in the formaldehyde solution is 40%.
[0045] (5) The carbon-encapsulated porous hard carbon / Si composite material precursor is placed in a tubular furnace, heated to 300°C at a heating rate of 5°C / min and kept warm for 1 hour, then heated to 800°C at the same heating rate and kept warm for 3 hours, and the product is collected to obtain a carbon-encapsulated porous hard carbon / Si composite material.
[0046] (6) Weigh 0.3 g of the carbon-encapsulated porous hard carbon / Si composite material obtained in step (5) as an active material, 0.1 g of conductive carbon black as a conductive agent, and 0.1 g of sodium alginate as a binder, place them in a mortar and grind them thoroughly, then use a dropper to add an appropriate amount of deionized water to a beaker and continue grinding to form a negative electrode material.
[0047] (7) The negative electrode material obtained in step (6) is coated on the current collector at a thickness of 15 μm, and then placed in a vacuum drying oven and dried at 80° C. for 12 hours to obtain a negative electrode sheet for a lithium-ion battery.
[0048] from Figure 1 It can be clearly seen that the nano-silicon particles have entered the pore channels of the porous hard carbon, and the pore channels of the porous hard carbon can alleviate the volume expansion of silicon. Figure 2 It shows that the porous hard carbon morphology can no longer be seen in the carbon-encapsulated porous hard carbon / Si composite material. A large number of silicon particles are encapsulated in the coating layer. The carbon encapsulation layer can alleviate the volume expansion of silicon. At the same time, it can also reduce the direct contact between silicon and the electrolyte, reduce the formation of the solid electrolyte (SEI) film, and reduce the consumption of lithium ions, thereby increasing the cycle stability of lithium-ion batteries. Figure 3 It can be seen that the Si in the porous hard carbon / Si composite material and the carbon-encapsulated porous hard carbon / Si composite material maintains a crystalline structure, and the porous hard carbon is an amorphous structure, which indicates that during the preparation process of the Si / porous HC (hard carbon for short HC) composite material, the crystal structure of the nano-silicon particles was well preserved and did not change.
[0049] Example 2
[0050] A method for preparing a negative electrode material for a lithium-ion battery by carbon encapsulating porous hard carbon / Si composite, specifically comprising the following steps:
[0051] (1) Weigh 10 g of birch sawdust and place it in 250 mL of a 0.8 mol / L potassium hydroxide solution. Cover the beaker with plastic wrap, control the temperature to 80 °C, and stir on a magnetic stirrer for 8 h. After the reaction is completed, pour off the upper solution, add deionized water and rinse repeatedly 2-3 times. Dry the sawdust in an 80 °C drying oven for 12 h, place it in a tubular furnace, heat it to 300 °C at a rate of 5 °C / min under an argon atmosphere, and keep it warm for 1 h. Then continue to heat it to 900 °C and start calcining. Calcinate for 0.5 h, soak the intermediate product in 2 mol / L hydrochloric acid for 24 hours, rinse it with deionized water, and finally dry it to obtain a porous hard carbon material. The pore size of the porous hard carbon is between 500 nm and 1 μm.
[0052] (2) 0.6 g of nano-silicon was placed in a mixed solution of 50 mL of anhydrous ethanol and 10 mL of deionized water, and ultrasonically vibrated for 1 hour to obtain a nano-silicon dispersion solution; at the same time, 0.6 g of porous hard carbon was placed in a mixed solution of 50 mL of anhydrous ethanol and 10 mL of deionized water, and ultrasonically vibrated for 1 hour to obtain a porous hard carbon dispersion solution.
[0053] (3) The porous hard carbon dispersion solution is stirred in a magnetic stirrer, and the nano-silicon dispersion solution is slowly added and stirred for 2 hours to obtain a porous hard carbon / Si composite material mixed solution, which is stirred continuously for subsequent steps.
[0054] (4) Add 6 g of carbon nanospheres to the continuously stirred porous hard carbon / Si composite material mixed solution, stir for 2 h, then add 3.6 g of hexadecyltrimethylammonium bromide (CTAB); continue stirring for 20 min, then add 10 mL of ammonia water and 4.2 g of m-aminophenol; continue stirring for 30 min, then add 9 mL of formaldehyde solution, seal, continue stirring at a reaction temperature of 40°C for 4 h, let stand for 4 h, centrifuge, wash the intermediate product twice with anhydrous ethanol, and dry it in a drying oven at 80°C for 12 h to obtain a carbon-encapsulated porous hard carbon / Si composite material precursor, wherein the mass percentage of ammonia in the ammonia water is 38%, and the mass percentage of formaldehyde in the formaldehyde solution is 40%.
[0055] (5) The carbon-encapsulated porous hard carbon / Si composite material precursor is placed in a tubular furnace, heated to 400°C at a heating rate of 5°C / min and kept warm for 0.2 h, then heated to 900°C at the same heating rate and kept warm for 1 h, and the product is collected to obtain a carbon-encapsulated porous hard carbon / Si composite material.
[0056] (6) Weigh 0.3 g of the carbon-encapsulated porous hard carbon / Si composite material obtained in step (5) as an active material, 0.1 g of conductive carbon black as a conductive agent, and 0.1 g of sodium alginate as a binder, place them in a mortar and grind them thoroughly, then use a dropper to add an appropriate amount of deionized water to a beaker and continue grinding to form a negative electrode material.
[0057] (7) The negative electrode material obtained in step (6) is coated on the current collector at a thickness of 15 μm, and then placed in a vacuum drying oven and dried at 80° C. for 12 hours to obtain a negative electrode sheet for a lithium-ion battery.
[0058] The performance of the negative electrode sheet of the lithium ion battery prepared in this embodiment is similar to that of embodiment 1.
[0059] Example 3
[0060] A method for preparing a negative electrode material for a lithium-ion battery by carbon encapsulating porous hard carbon / Si composite, specifically comprising the following steps:
[0061] (1) Weigh 10 g of birch sawdust and place it in 250 mL of a 2 mol / L potassium hydroxide solution. Cover the beaker with plastic wrap, control the temperature to 70 °C, and stir on a magnetic stirrer for 4 h. After the reaction is complete, pour off the upper solution, add deionized water and rinse repeatedly 2-3 times. Dry the sawdust in an 80 °C drying oven for 12 h, place it in a tubular furnace, heat it to 500 °C at a rate of 5 °C / min under an argon atmosphere, and keep it warm for 0.2 h. Then continue to heat it to 700 °C and start calcining. Calcinate for 3 h, soak the intermediate product in 2 mol / L hydrochloric acid for 12 hours, rinse it with deionized water, and finally dry it to obtain a porous hard carbon material. The pore size of the porous hard carbon is between 500 nm and 1 μm.
[0062] (2) 0.3 g of nano-silicon was placed in a mixed solution of 25 mL of anhydrous ethanol and 25 mL of deionized water, and ultrasonically vibrated for 1 hour to obtain a nano-silicon dispersion solution; at the same time, 0.1 g of porous hard carbon was placed in a mixed solution of 25 mL of anhydrous ethanol and 25 mL of deionized water, and ultrasonically vibrated for 1 hour to obtain a porous hard carbon dispersion solution.
[0063] (3) The porous hard carbon dispersion solution is stirred in a magnetic stirrer, and the nano-silicon dispersion solution is slowly added and stirred for 2 hours to obtain a porous hard carbon / Si composite material mixed solution, which is stirred continuously for subsequent steps.
[0064] (4) Add 0.3 g of carbon nanospheres to the continuously stirred porous hard carbon / Si composite material mixed solution, stir for 2 h, then add 0.3 g of hexadecyltrimethylammonium bromide (CTAB); continue stirring for 20 min, then add 2 mL of ammonia water and 0.6 g of m-aminophenol; continue stirring for 30 min, then add 1.2 mL of formaldehyde solution, seal, continue stirring at a reaction temperature of 40°C for 12 h, let stand for 1 h, centrifuge, wash the intermediate product twice with anhydrous ethanol, and dry it in a drying oven at 80°C for 12 h to obtain a carbon-encapsulated porous hard carbon / Si composite material precursor, wherein the mass percentage of ammonia in the ammonia water is 38%, and the mass percentage of formaldehyde in the formaldehyde solution is 40%.
[0065] (5) The carbon-encapsulated porous hard carbon / Si composite material precursor is placed in a tubular furnace, heated to 500°C at a heating rate of 5°C / min and kept warm for 0.1 h, then heated to 700°C at the same heating rate and kept warm for 3 h, and the product is collected to obtain a carbon-encapsulated porous hard carbon / Si composite material.
[0066] (6) Weigh 0.3 g of the carbon-encapsulated porous hard carbon / Si composite material obtained in step (5) as an active material, 0.1 g of conductive carbon black as a conductive agent, and 0.1 g of sodium alginate as a binder, place them in a mortar and grind them thoroughly, then use a dropper to add an appropriate amount of deionized water to a beaker and continue grinding to form a negative electrode material.
[0067] (7) The negative electrode material obtained in step (6) is coated on the current collector at a thickness of 15 μm, and then placed in a vacuum drying oven and dried at 80° C. for 24 hours to obtain a negative electrode sheet for a lithium-ion battery.
[0068] The performance of the negative electrode sheet of the lithium ion battery prepared in this embodiment is similar to that of embodiment 1.
[0069] Comparative Example 1
[0070] The only difference between the preparation method of a negative electrode material for a lithium ion battery in this comparative example and the preparation method of a negative electrode material for a carbon-encapsulated porous hard carbon / Si composite lithium ion battery in Example 1 is that no porous hard carbon is added. The specific steps are as follows:
[0071] (1) 0.3 g of nano-silicon was placed in a mixed solution of 40 mL of anhydrous ethanol and 10 mL of deionized water, and ultrasonically vibrated for 1 h to obtain a nano-silicon dispersion solution.
[0072] (2) Add 0.9 g of carbon nanospheres to the continuously stirred nano-silicon dispersion solution, and add 0.4 g of hexadecyltrimethylammonium bromide (CTAB) after stirring for 2 h; continue stirring for 20 min, add 4 mL of ammonia water and 1.2 g of m-aminophenol; continue stirring for 30 min, add 1.6 mL of formaldehyde solution, seal, continue stirring at a reaction temperature of 40°C for 8 h, let stand for 4 h, centrifuge, wash the intermediate product twice with anhydrous ethanol, and dry it in a drying oven at 80°C for 12 h to obtain a carbon-encapsulated Si composite material precursor, wherein the mass percentage of ammonia in the ammonia water is 38%, and the mass percentage of formaldehyde in the formaldehyde solution is 40%.
[0073] (3) The carbon-encapsulated Si composite material precursor is placed in a tubular furnace, heated to 300°C at a heating rate of 5°C / min and kept warm for 1 hour, then heated to 800°C at the same heating rate and kept warm for 3 hours, and the product is collected to obtain a carbon-encapsulated Si composite material.
[0074] (4) Weigh 0.3 g of the carbon-encapsulated Si composite material obtained in step (3) as an active material, 0.1 g of conductive carbon black as a conductive agent, and 0.1 g of sodium alginate as a binder, place them in a mortar and grind them thoroughly, then add an appropriate amount of deionized water to a beaker with a dropper and continue grinding to form a negative electrode material.
[0075] (5) The negative electrode material obtained in step (4) is coated on the current collector at a thickness of 15 μm, and then placed in a vacuum drying oven and dried at 80° C. for 12 hours to obtain a negative electrode sheet for a lithium-ion battery.
[0076] Comparative Example 2
[0077] The only difference between the method for preparing a negative electrode material for a lithium ion battery in this comparative example and the method for preparing a negative electrode material for a carbon-encapsulated porous hard carbon / Si composite lithium ion battery in Example 1 is that CTAB is not added in step (4). The specific steps are as follows:
[0078] (1) Weigh 10 g of birch sawdust and place it in 250 mL of a 1 mol / L potassium hydroxide solution. Cover the beaker with plastic wrap, control the temperature to 80 °C, and stir on a magnetic stirrer for 8 h. After the reaction is completed, pour off the upper solution, add deionized water and rinse repeatedly 2-3 times. Dry the sawdust in an 80 °C drying oven for 12 h, place it in a tubular furnace, heat it to 300 °C at a rate of 5 °C / min under an argon atmosphere, and keep it warm for 0.5 h. Then continue to heat it to 800 °C and start calcining. Calcinate for 1 h, soak the intermediate product in 1 mol / L hydrochloric acid for 24 hours, rinse it with deionized water, and finally dry it to obtain a porous hard carbon material. The pore size of the porous hard carbon is between 500 nm and 1 μm.
[0079] (2) 0.3 g of nano-silicon was placed in a mixed solution of 40 mL of anhydrous ethanol and 10 mL of deionized water, and ultrasonically vibrated for 1 hour to obtain a nano-silicon dispersion solution; at the same time, 0.2 g of porous hard carbon was placed in a mixed solution of 40 mL of anhydrous ethanol and 10 mL of deionized water, and ultrasonically vibrated for 1 hour to obtain a porous hard carbon dispersion solution.
[0080] (3) The porous hard carbon dispersion solution is stirred in a magnetic stirrer, and the nano-silicon dispersion solution is slowly added and stirred for 2 hours to obtain a porous hard carbon / Si composite material mixed solution, which is stirred continuously for subsequent steps.
[0081] (4) Add 0.9 g of carbon nanospheres to the continuously stirred porous hard carbon / Si composite material mixed solution, stir for 2 h, then add 4 mL of ammonia water and 1.2 g of m-aminophenol; continue stirring for 30 min, then add 1.6 mL of formaldehyde solution, seal, continue stirring at a reaction temperature of 40°C for 8 h, let stand for 4 h, centrifuge, wash the intermediate product twice with anhydrous ethanol, and dry it in a drying oven at 80°C for 12 h to obtain a carbon-encapsulated porous hard carbon / Si composite material precursor, wherein the mass percentage of ammonia in the ammonia water is 38%, and the mass percentage of formaldehyde in the formaldehyde solution is 40%.
[0082] (5) The carbon-encapsulated porous hard carbon / Si composite material precursor is placed in a tubular furnace, heated to 300°C at a heating rate of 5°C / min and kept warm for 1 hour, then heated to 800°C at the same heating rate and kept warm for 3 hours, and the product is collected to obtain a carbon-encapsulated porous hard carbon / Si composite material.
[0083] (6) Weigh 0.3 g of the carbon-encapsulated porous hard carbon / Si composite material obtained in step (5) as an active material, 0.1 g of conductive carbon black as a conductive agent, and 0.1 g of sodium alginate as a binder, place them in a mortar and grind them thoroughly, then add an appropriate amount of deionized water to a beaker with a dropper and continue grinding to form a negative electrode material.
[0084] (7) The negative electrode material obtained in step (6) is coated on the current collector at a thickness of 15 μm, and then placed in a vacuum drying oven and dried at 80° C. for 12 hours to obtain a negative electrode sheet for a lithium-ion battery.
[0085] Comparative Example 3
[0086] The only difference between the method for preparing a negative electrode material for a lithium ion battery in this comparative example and the method for preparing a negative electrode material for a carbon-encapsulated porous hard carbon / Si composite lithium ion battery in Example 1 is that carbon nanospheres are not added in step (4). The specific steps are as follows:
[0087] (1) Weigh 10 g of birch sawdust and place it in 250 mL of a 1 mol / L potassium hydroxide solution. Cover the beaker with plastic wrap, control the temperature to 80 °C, and stir on a magnetic stirrer for 8 h. After the reaction is completed, pour off the upper solution, add deionized water and rinse repeatedly 2-3 times. Dry the sawdust in an 80 °C drying oven for 12 h, place it in a tubular furnace, heat it to 800 °C at a rate of 5 °C / min under an argon atmosphere, and then start calcining. Calcinate for 1 h, soak the intermediate product in 1 mol / L hydrochloric acid for 24 hours, rinse it with deionized water, and finally dry it to obtain a porous hard carbon material. The pore size of the porous hard carbon is between 500 nm and 1 μm.
[0088] (2) 0.3 g of nano-silicon was placed in a mixed solution of 40 mL of anhydrous ethanol and 10 mL of deionized water, and ultrasonically vibrated for 1 hour to obtain a nano-silicon dispersion solution; at the same time, 0.2 g of porous hard carbon was placed in a mixed solution of 40 mL of anhydrous ethanol and 10 mL of deionized water, and ultrasonically vibrated for 1 hour to obtain a porous hard carbon dispersion solution.
[0089] (3) The porous hard carbon dispersion solution is stirred in a magnetic stirrer, and the nano-silicon dispersion solution is slowly added and stirred for 2 hours to obtain a porous hard carbon / Si composite material mixed solution, which is stirred continuously for subsequent steps.
[0090] (4) Add 0.4 g of hexadecyltrimethylammonium bromide (CTAB) to the continuously stirred porous hard carbon / Si composite material mixed solution, stir for 20 min, add 4 mL of ammonia water and 1.2 g of m-aminophenol; continue stirring for 30 min, add 2.4 mL of formaldehyde solution, seal, continue stirring at a reaction temperature of 40°C for 8 h, let stand for 4 h, centrifuge, wash the intermediate product twice with anhydrous ethanol, and dry it in a drying oven at 80°C for 12 h to obtain a carbon-encapsulated porous hard carbon / Si composite material precursor, the mass percentage of ammonia in the ammonia water is 38%, and the mass percentage of formaldehyde in the formaldehyde solution is 40%.
[0091] (5) The carbon-encapsulated porous hard carbon / Si composite material precursor is placed in a tubular furnace, heated to 300°C at a heating rate of 5°C / min and kept warm for 1 hour, then heated to 800°C at the same heating rate and kept warm for 3 hours, and the product is collected to obtain a carbon-encapsulated porous hard carbon / Si composite material.
[0092] (6) Weigh 0.3 g of the carbon-encapsulated porous hard carbon / Si composite material obtained in step (5) as an active material, 0.1 g of conductive carbon black as a conductive agent, and 0.1 g of sodium alginate as a binder, place them in a mortar and grind them thoroughly, then add an appropriate amount of deionized water to a beaker with a dropper and continue grinding to form a negative electrode material.
[0093] (7) The negative electrode material obtained in step (6) is coated on the current collector at a thickness of 15 μm, and then placed in a vacuum drying oven and dried at 80° C. for 12 hours to obtain a negative electrode sheet for a lithium-ion battery.
[0094] Comparative Example 4
[0095] A method for preparing a negative electrode material for a lithium-ion battery by carbon encapsulating porous hard carbon / Si composite, specifically comprising the following steps:
[0096] (1) Weigh 10 g of birch sawdust and place it in 250 mL of a 1 mol / L potassium hydroxide solution. Cover the beaker with plastic wrap, control the temperature to 80 °C, and stir on a magnetic stirrer for 8 h. After the reaction is completed, pour off the upper solution, add deionized water and rinse repeatedly 2-3 times. Dry the sawdust in an 80 °C drying oven for 12 h, place it in a tubular furnace, heat it to 300 °C at a rate of 5 °C / min under an argon atmosphere, and keep it warm for 0.5 h. Then continue to heat it to 800 °C and start calcining. Calcinate for 1 h, soak the intermediate product in 1 mol / L hydrochloric acid for 24 hours, rinse it with deionized water, and finally dry it to obtain a porous hard carbon material. The pore size of the porous hard carbon is between 500 nm and 1 μm.
[0097] (2) 0.3 g of nano-silicon was placed in a mixed solution of 40 mL of anhydrous ethanol and 10 mL of deionized water, and ultrasonically vibrated for 1 hour to obtain a nano-silicon dispersion solution; at the same time, 0.2 g of porous hard carbon was placed in a mixed solution of 40 mL of anhydrous ethanol and 10 mL of deionized water, and ultrasonically vibrated for 1 hour to obtain a porous hard carbon dispersion solution.
[0098] (3) The porous hard carbon dispersion solution is stirred in a magnetic stirrer, and the nano-silicon dispersion solution is slowly added and stirred for 2 hours to obtain a porous hard carbon / Si composite material mixed solution. After continuous stirring, the solution is dried in a drying oven at 80°C for 12 hours to obtain a porous hard carbon / Si composite material.
[0099] (4) Weigh 0.3 g of the carbon-encapsulated porous hard carbon / Si composite material obtained in step (3) as an active material, 0.1 g of conductive carbon black as a conductive agent, and 0.1 g of sodium alginate as a binder, place them in a mortar and grind them thoroughly, then use a dropper to add an appropriate amount of deionized water to a beaker and continue grinding to form a negative electrode material.
[0100] (5) The negative electrode material obtained in step (4) is coated on the current collector at a thickness of 15 μm, and then placed in a vacuum drying oven and dried at 80° C. for 12 hours to obtain a negative electrode sheet for a lithium-ion battery.
[0101] Effect example
[0102] The negative electrode plates of the lithium-ion batteries in Examples 1-3 and Comparative Examples 1-4 were assembled into batteries, CR2032 button batteries were selected, glass fiber separators were selected as battery diaphragms, the electrolyte was 1 mol / L LiPF6 dissolved in a mixed solution of EC / DEC with a volume ratio of 1:1, and 1.0 mol / L LiPF6 dissolved in a mixed solution of EC / DEC / DMC with a volume ratio of 1:1:1 was added as an additive; after the batteries were packaged, they were left to stand for 24 hours, and then their performance was tested.
[0103] Through testing, such as Figure 4 As shown, at a current density of 0.2 A / g, the battery capacity retention rates of Example 1 and Comparative Example 3 after 150 cycles are 54.41% and 44.06%, respectively, compared with 15.5%, 19.17% and 22.74% of Comparative Examples 1, 2 and 4, respectively, having good cycle stability and capacity retention rate. Figure 5By comparing Example 1 and Comparative Example 3, which have better cycle stability, it can be seen from the figure that Comparative Example 3 shows a relatively excellent discharge specific capacity at a low current density, but the capacity decreases seriously at a high current density, especially at a current density of 2A / g, the battery fails. Example 1 still has a capacity of more than 490mAh / g and 400mAh / g at current densities of 1A / g and 2A / g. When the current density returns to 0.1A / g, the capacity decay is very small, and it has good rate performance. Figure 6 The long cycle discharge performance curves of Example 1 and Comparative Example 3 at a current density of 1A / g are shown. The overall cycle curve of Comparative Example 3 is relatively stable. After 65 cycles, the capacity reaches a peak value of 420mAh / g. The capacity continues to decay in the subsequent cycles, and the capacity retention rate is 35.02% after 500 cycles. The battery capacity of Example 1 gradually rises and stabilizes at 520mAh / g. After 500 cycles at high current density, the capacity remains at 45.93%. Compared with Comparative Example 3, the addition of carbon nanospheres enables Example 1 to have good electronic conductivity and ionic conductivity, so that nano silicon can be fully utilized, and the high capacity characteristics of silicon can be brought into play at high current density, and excellent cycle stability is shown. Comparative Examples 1, 2, and 4 have low capacity and severe decay during high current cycles. Since Comparative Example 1 does not have a porous hard carbon skeleton as support, the volume expansion of silicon during the cycle causes the battery capacity to be low and continuously decline. Since hexadecyltrimethylammonium bromide was not added in Comparative Example 2, the composite structure obtained was a carbon encapsulation layer that was only a thin carbon layer coated on the surface of the nano-silicon, and the porous hard carbon and nano-silicon could not be encapsulated as a whole. During the high current cycle, the outer carbon layer was very easy to break, resulting in capacity decay. In Comparative Example 4, the electrolyte would directly contact the silicon, causing irreversible loss of capacity. During the high current cycle process, the simple composite structure failed to improve the conductivity of the material itself, so that the charge could not pass through the silicon material and the charging and discharging was terminated, so the capacity could not be manifested. In summary, the carbon-encapsulated porous hard carbon / Si composite material described in the present invention has good cycle stability, battery capacity, and rate performance. Compared with the comparative example, whether it is cycle stability, battery capacity, or rate performance, it has good conductivity and great development prospects.
[0104] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a carbon-encapsulated porous hard carbon / Si composite negative electrode material, characterized in that: The steps include: (1) Sawdust and potassium hydroxide powder are placed in water, sealed, stirred, dried, and then calcined under protective gas. The calcined product is then soaked in hydrochloric acid, rinsed, and finally dried to obtain porous hard carbon. (2) dissolving nano-silicon in a mixture of anhydrous ethanol and water to obtain a nano-silicon solution; dispersing porous hard carbon in a mixture of anhydrous ethanol and water to obtain a porous hard carbon dispersion solution; (3) mixing the nano-silicon solution and the porous hard carbon dispersion solution to obtain a porous hard carbon / Si composite material mixed solution; (4) adding carbon nanospheres, hexadecyltrimethylammonium bromide, ammonia water, m-aminophenol and formaldehyde solution to the porous hard carbon / Si composite material mixed solution continuously stirred in step (3), sealing, stirring, standing, centrifuging, washing and drying to obtain a carbon-encapsulated porous hard carbon / Si composite material precursor; (5) calcining the carbon-encapsulated porous hard carbon / Si composite material precursor in a protective gas to obtain a carbon-encapsulated porous hard carbon / Si composite material; (6) The carbon-encapsulated porous hard carbon / Si composite material, the conductive agent, and the binder are mixed to prepare a slurry, and then coated on a current collector and dried to obtain a negative electrode sheet for a lithium-ion battery.
2. The method for preparing the carbon-encapsulated porous hard carbon / Si composite negative electrode material according to claim 1, characterized in that: The mass ratio of the carbon nanospheres, hexadecyltrimethylammonium bromide, ammonia water, m-aminophenol, formaldehyde and nano-silicon is (1-10):(1-6):(6-15):(2-7):(4-15):
1.
3. The method for preparing the carbon-encapsulated porous hard carbon / Si composite negative electrode material according to claim 1, characterized in that: The diameter of the carbon nanospheres is 20-100 nm, the mass percentage of ammonia in the ammonia water is 38%, and the mass percentage of formaldehyde in the formaldehyde solution is 40%.
4. The method for preparing the carbon-encapsulated porous hard carbon / Si composite negative electrode material according to claim 1, characterized in that: The order in which the carbon nanospheres, hexadecyltrimethylammonium bromide, ammonia water, m-aminophenol and formaldehyde solution are added to the porous hard carbon / Si composite material mixed solution is carbon nanospheres, hexadecyltrimethylammonium bromide, ammonia water, m-aminophenol and formaldehyde solution; the interval time for adding the materials is 10 to 180 minutes, and the reaction is continued for 4 to 12 hours after the materials are added.
5. The method for preparing the carbon-encapsulated porous hard carbon / Si composite negative electrode material according to claim 1, characterized in that: The mass ratio of the sawdust to the potassium hydroxide powder is (1-2):(1-3); after the sawdust and the potassium hydroxide powder are put into water, the concentration of potassium hydroxide is 0.8-2.0 mol / L.
6. The method for preparing the carbon-encapsulated porous hard carbon / Si composite negative electrode material according to claim 1, characterized in that: In the step (1), the calcination specifically comprises: heating from room temperature to 300-500° C. at a heating rate of 5° C. / min and keeping the temperature for 0.2-1 h, and then heating to 700-900° C. and keeping the temperature for 0.5-3 h.
7. The method for preparing the carbon-encapsulated porous hard carbon / Si composite negative electrode material according to claim 1, characterized in that: In the step (2), the volume ratio of anhydrous ethanol to water is (1-5):
1.
8. The method for preparing the carbon-encapsulated porous hard carbon / Si composite negative electrode material according to claim 1, characterized in that: In the step (3), the mass ratio of nano-silicon to porous hard carbon is (1-3):
1.
9. The method for preparing the carbon-encapsulated porous hard carbon / Si composite negative electrode material according to claim 1, characterized in that: In the step (5), the calcination specifically includes: heating from room temperature to 300-500° C. at a heating rate of 5° C. / min and keeping the temperature for 0.1-1 h, and then heating to 700-900° C. and keeping the temperature for 1-3 h.
10. The method for preparing the carbon-encapsulated porous hard carbon / Si composite negative electrode material according to claim 1, characterized in that: The conductive agent is conductive carbon black; the binder is sodium alginate; the mass ratio of the carbon-encapsulated porous hard carbon / Si composite material, the conductive agent and the binder is 6:2:2.
Citation Information
Patent Citations
A method for preparing C-SiC-Si composite negative electrode material for lithium ion battery
CN115377399B
Negative electrode material, preparation method thereof and lithium ion battery
CN117317205A
Method for improving utilization rate of carbon-coated silicon oxide and its products and applications
CN118117082B
Lithium ion battery silicon-carbon negative electrode and preparation method thereof
CN118610384A
Lithium ion battery silicon and silicon alloy composite negative electrode material and preparation method thereof
CN118645600A
Cited By
Preparation method of porous carbon-silicon composite negative electrode material of lithium battery and lithium battery
CN120432517A